Biocompatible, bacteria-targeting resveratrol nanoparticles fabricated by Mannich molecular condensation for accelerating infected wound healing. Issue 44 (7th November 2022) - Tang, Liwen; Chen, Xiangyu; Tong, Qiulan; Ran, Yaqin; Ma, Lei; Tan, Yunfei; Yi, Zeng; Li, Xudong
Abstract : Antioxidative, anti-inflammatory and targeted antibacterial resveratrol nanoparticle-loaded hydrogels (Res NPs/Gel) accelerate infected wound healing. Abstract : Excessive reactive oxygen species (ROS) and long-term inflammation can delay wound healing and cause tissue damage, while bacterial infection aggravates the wound environment further. It is impossible to resolve all these thorny problems simultaneously with a wound dressing that has only one function. The antioxidative and anti-inflammatory properties of resveratrol (Res) have been proven. However, the effect of Res is non-selective, and high levels of Res can inhibit cell growth and promote oxidation. Res is also difficult to dissolve and possesses insufficient antibacterial properties, so its role is limited. In this study, Res was assembled via Mannich reaction into nanoparticles and functionalized by phenylboric acid, giving rise to targeting bacteria and solving the water-insoluble dilemma of Res. In comparison with Trolox, the assembled Res NPs performed better at scavenging ABTS and DPPH free radicals. Furthermore, Res NPs that targeted bacteria also showed high biocompatibility at concentrations five times higher than pure Res. The activities of Res NPs were comparable to free Res in downregulating the expression of inflammatory cytokines, and reducing intracellular excessive ROS. The gel embedded with Res NPs accelerated the formation of granulation tissue, collagen deposition, and re-epithelialization, facilitating wound healing. The present study suggests that functionalized polyphenol-based materials are preferably suited to the development of tissue engineering biomaterials.